2019
DOI: 10.26464/epp2019036
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale dipolarization fronts in the Earth′s magnetotail

Abstract: Previous studies suggest that dipolarization fronts (DFs) are 1 to 3R E (R E is the earth radius) wide in the dawn‐dusk direction. Recent kinetic simulations have found that DFs may break up into small‐scale structures after they are produced by reconnection. Motivated by this simulation, we revisited the scale size of DFs in the dawn‐dusk direction by using Cluster observations during the years when the inter‐distance among Cluster spacecraft was between 1000 and 2000 km. We selected the DFs that were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…For the ion scale of the DF, statistical studies have shown that the thickness of the DF was ∼1.7–1.8 ion inertial length (e.g., Fu et al., 2012b; J. Liu et al., 2013; Schmid et al., 2011). DFs with ion‐scale in the dawn‐dusk direction were also reported recently (J. Huang et al., 2019). Runov et al.…”
Section: Introductionsupporting
confidence: 76%
“…For the ion scale of the DF, statistical studies have shown that the thickness of the DF was ∼1.7–1.8 ion inertial length (e.g., Fu et al., 2012b; J. Liu et al., 2013; Schmid et al., 2011). DFs with ion‐scale in the dawn‐dusk direction were also reported recently (J. Huang et al., 2019). Runov et al.…”
Section: Introductionsupporting
confidence: 76%
“…We should note that our simulation is 2.5‐D, which neglects any variations in the Y direction (the out‐of‐plane direction). However, significant variations in the Y direction are seen on the DF due to the cross‐tail instabilities developed on the front surface (Huang et al, 2019; Lapenta et al, 2014; Pritchett, 2016), which leads to an alternative sign of J · E along the surface of the DF. This 3‐D effect may also lead to the sign change of Pi‐D in Y.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Similar events have also been reported in simulations (Haynes et al, 2015; Roytershteyn et al, 2015) and observations (Huang SY et al, 2017a, b). These structures, including recently reported kinetic‐scale flux ropes (Huang SY et al, 2016; Matsui et al, 2019; Sun WJ et al, 2019; Wang SM et al, 2019; Yao ST et al, 2020b) and kinetic‐scale magnetic dips and peaks (Hellinger and Štverák, 2018; Stawarz et al, 2018; Yao ST et al, 2018a; Hoilijoki et al, 2019), are new types of coherent structures found in turbulent plasmas, and play important roles in the cascade of turbulence from ion to electron scales (e.g., Huang J et al, 2019; Lucek et al, 2005; Karimabadi et al, 2014; Sahraoui et al, 2020; Shang WS et al, 2020). Yao ST et al (2019a) found that these KSMHs are coupled with electron cyclotron waves, electrostatic solitary waves, and whistler mode waves (Li Z et al, 2019).…”
Section: Introductionmentioning
confidence: 99%